Transcriptome assembly and annotation of johnsongrass (Sorghum halepense) rhizomes identify candidate rhizome‐specific genes. (19th June 2018) - Ryder, Nathan; Dorn, Kevin M.; Huitsing, Mark; Adams, Micah; Ploegstra, Jeff; DeHaan, Lee; Larson, Steve; Tintle, Nathan L.
Abstract: Rhizomes facilitate the wintering and vegetative propagation of many perennial grasses. Sorghum halepense (johnsongrass) is an aggressive perennial grass that relies on a robust rhizome system to persist through winters and reproduce asexually from its rootstock nodes. This study aimed to sequence and assemble expressed transcripts within the johnsongrass rhizome. A de novo transcriptome assembly was generated from a single johnsongrass rhizome meristem tissue sample. A total of 141, 176 probable protein‐coding sequences from the assembly were identified and assigned gene ontology terms using Blast2GO. Estimated expression analysis and BLAST results were used to reduce the assembly to 64, 447 high‐confidence sequences. The johnsongrass assembly was compared to Sorghum bicolor, a related nonrhizomatous species, along with an assembly of similar rhizome tissue from the perennial grain crop Thinopyrum intermedium . The presence/absence analysis yielded a set of 98 expressed johnsongrass contigs that are likely associated with rhizome development.